Enrichment of rare methanogenic Archaea shows their important ecological role in natural high-CO2 terrestrial subsurface environments - Jia, Zeyu; Lipus, Daniel; Burckhardt, Oliver; Bussert, Robert; Sondermann, Megan; Bartholomäus, Alexander; Wagner, Dirk; Kallmeyer, Jens (Frontiers in Microbiology, 2023)
Long-term stability of underground CO2 storage is partially affected by microbial activity but our knowledge of these effects is limited, mainly due to a lack of sites. A consistently high flux of mantle-derived CO2 makes the Eger Rift in the Czech Republic a natural analogue to underground CO2 storage. The Eger Rift is a seismically active region and H2 is produced abiotically during earthquakes, providing energy to indigenous microbial communities. To investigate the response of a microbial ecosystem to high levels of CO2 and H2, we enriched microorganisms from samples from a 239.5 m long drill core from the Eger Rift. Microbial abundance, diversity and community structure were assessed using qPCR and 16S rRNA gene sequencing. Enrichment cultures were set up with minimal mineral media and H2/CO2 headspace to simulate a seismically active period with elevated H2. Methane headspace concentrations in the enrichments indicated that active methanogens were almost exclusively restricted to enrichment cultures from Miocene lacustrine deposits (50-60 m), for which we observed the most significant growth. Taxonomic assessment showed microbial communities in these enrichments to be less diverse than those with little or no growth. Active enrichments were especially abundant in methanogens of the taxa Methanobacterium and Methanosphaerula. Concurrent to the emergence of methanogenic Archaea, we also observed sulfate reducers with the metabolic ability to utilize H2 and CO2, specifically the genus Desulfosporosinus, which were able to outcompete methanogens in several enrichments. Low microbial abundance and a diverse non-CO2 driven microbial community, similar to that in drill core samples, also reflect the inactivity in these cultures. Significant growth of sulfate reducing and methanogenic microbial taxa, which make up only a small fraction of the total microbial community, emphasize the need to account for rare biosphere taxa when assessing the metabolic potential of microbial subsurface populations. The observation that CO2 and H2-utilizing microorganisms could only be enriched from a narrow depth interval suggests that factors such as sediment heterogeneity may also be important. This study provides new insight on subsurface microbes under the influence of high CO2 concentrations, similar to those found in CCS sites.